Influence of gut microbiota and immune markers in different stages of colorectal adenomas - Wang, Xianmei; Chen, Hang; Yang, Meng; Huang, Minshan; Zhang, Dan; Li, Mingke; Wang, Hui; Zhou, Qingqing; Lu, Lihong; Li, Yu; Yu, Jiangkun; Ma, Lanqing (Frontiers in Microbiology, 2025)
ObjectiveColorectal adenomas (CRA) are the primary precancerous lesions leading to colorectal cancer (CRC). Early detection and intervention of CRA can significantly reduce the incidence of CRC. We investigated the relationships between the gut microbiome and the expression levels of PD-L1, IL-6, and IFN-γ at different CRA stages.MethodsParticipants were divided into normal, non-advanced adenoma (NAA), and advanced adenoma (AA) groups. PD-L1 expression in collected tissues was analyzed via immunohistochemistry (IHC) and Western blotting. Serum IL-6 and IFN-γ levels were measured using Enzyme-Linked Immunosorbent Assay (ELISA). 16S rRNA gene sequencing was used to examine gut microbiota changes, with correlation analysis to assess microbial influences on CRA progression.ResultsThe main differences in bacterial composition among the three groups were found within the Firmicutes and Bacteroidetes phyla. In the normal vs. NAA comparison, Clostridium sensu stricto, Faecalimonas, Gemmiger, and Ruminococcus were more abundant in the normal group, while Solobacterium was enriched in the NAA group. For the normal vs. AA comparison, the normal group was enriched with Anaerostipes, Blautia, Clostridium sensu stricto, Intestinibacter, Phocaeicola, and Turicibacter, whereas Solobacterium was more abundant in the AA group. In the NAA vs. AA comparison, the NAA group exhibited higher levels of Blautia, Faecalimonas, and Turicibacter relative to the AA group. Anaerostipes and Blautia are positively correlated with taurine and hypotaurine metabolism, propanoate metabolism, and zeatin biosynthesis. PD-L1 protein levels progressively increase with CRA advancement. Additionally, Faecalimonas, and Solobacterium were negatively associated with IFN-γ, while Gemmiger, and Anaerostipes were positively associated with IL-6.ConclusionThis study highlights the dynamic alterations in gut microbiota composition and their potential influence on the regulation of inflammatory cytokines and PD-L1 expression during CRA progression. The enrichment of protective taxa, such as Anaerostipes and Blautia, in the normal group emphasizes their potential role in mitigating adenoma progression. Dietary modulation to promote the proliferation of these beneficial bacteria could serve as a promising strategy to improve colorectal health. Future research should further explore the specific relationships between dietary components, gut microbiota, and metabolic pathways, and assess the effects of dietary interventions on gut health.